THE EFFECTS OF ECONOMIC RECESSION ON EDUCATION IN NIGERIA - Yenle, Mershak Shem (PEOPLE: International Journal of Social Sciences, 2017)
This paper examines the effects of economic recession on education especially in developing countries such as Nigeria. The paper x-rays the causes of recession to include: war, high banking interest rate poor fiscal powers, rising in oil price and bursting of housing. It goes further to look at some of the effects of economic recession to include: unemployment, lower wage, high taxation, budget deficit, rising bond yields and untold hardship on the people. The paper concludes by making recommendations such as funding of the education sector should be increased by encouraging the government to always enact long lasting policies and stand firm in staging war against corruption.